The Significance of the MSU Quranic League in Promoting al-Quran Awareness in Higher Education Institutions - Basirah Abu Bakar; Muhammad Nur Farhan Zamziba; Muhammad Amir Syakir Manja; Asma Syahamah Hamidi (Universiti Sains Islam Malaysia, 2026)
Journal of Quran Sunnah Education & Special Needs, Volume 9 Issue 2 Page (18–26)